The Perceptions Of Higher Education Academic Staff On The Freedom To Decide What To Teach - Kimoga, Joseph; Justine, Namaganda; Tom, Maigut; Constance, Asiimwe; Caroline, Ngabirano (Advances in Social Sciences Research Journal, 2017)
The common perception is that teachers have to teach according to what is laid out in the curriculum. Little is spent on reflecting on the effects of teaching a prescribed content to which design the practitioner did not contribute. This article is not refuting the existence of prescribed content for classroom interaction, but the freedom of the teacher in preferring parts of the content to teach. We set out to seek the perceptions of academic staff at higher education level on freedom to decide what to teach. We found that political interference is the major threat to the freedom of academic staff regarding the decision on the content. We conclude that there is lack of higher education policy regarding academic freedom to choose the content to teach, and there is also no specific internal policy to safeguard academic freedom. We recommend establishing institutional policies and national laws to foster academic freedom; promoting freedom of expression beyond constitutional rhetoric; and allowing free operation of higher education institutions.